Validation of the Spanish version of the Technostress Creators Scale in Chilean Workers - Salazar-Concha, Cristian; Ficapal-Cusí, Pilar; Peñarroja, Vicente; Enache-Zegheru, Mihaela (Anales de Psicología / Annals of Psychology, 2022)
The purpose of this study was to adapt and validate the Spanish version of the Technostress Creators Scale (TCS). The scale was administered to 1.047 Chilean professionals. The internal structure of the scale was tested by conducting exploratory and confirmatory factor analyses. The average variance extracted (AVE) and the Fornell–Larcker criterion were used to examine convergent and discriminant validity, respectively. To investigate concurrent validity, we focused on the relation between the TCS scale and role stress, which is a distinct, albeit conceptually related construct. Our findings supported a five-factor model consisting of 23 items distributed in five factors: techno-overload, techno-invasion, techno-complexity, techno-insecurity and techno-uncertainty. The Spanish version of the TCS had a high level of internal consistency, which was similar to the original scale. Appropriate evidence of concurrent validity was also shown. In addition, we conducted an international comparison of the research results with other relevant adaptations of the instrument reported in different cultural contexts. The results confirmed that the Spanish translation of the TCS is a suitable instrument for measuring technostress and can contribute to an empirical examination of this phenomenon in Spanish-speaking countries.